Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division dengan Pendekatan Contextual Learning terhadap Hasil Belajar Kelas IV UPTD SDN Demangan 1 - Wafiroh, Nihayatul; Perdana, Parrisca Indra (Yayasan Arrahman Nahdlatul Wathan, 2024)
This study aims to determine the effect of cooperative learning model type Student Teams Achievement Division (STAD) with Contextual Teaching and Learning approach on mathematics learning outcomes of class IV UPTD SDN Demangan 1. The research method used is quantitative with quasi experimental design in the form of nonequivalent control group. Sampling was done using nonprobability sampling technique purposive sampling type. The first sample is class IVB totaling 32 students as an experimental class which is given the treatment of a cooperative learning model of Student Teams Achievement Division (STAD) type with a Contextual Teaching and Learning approach. The second sample is class IVC as a control class which is given treatment like the way the teacher teaches in class, namely using a learning model, with 33 students. The results showed that there was an effect of the cooperative learning model of the Student Teams Achievement Division (STAD) type with a Contextual Teaching and Learning approach on the learning outcomes of mathematics class IV UPTD SDN Demangan 1.